2011
DOI: 10.1371/journal.pgen.1002258
|View full text |Cite
|
Sign up to set email alerts
|

Elongator Complex Influences Telomeric Gene Silencing and DNA Damage Response by Its Role in Wobble Uridine tRNA Modification

Abstract: Elongator complex is required for formation of the side chains at position 5 of modified nucleosides 5-carbamoylmethyluridine (ncm5U34), 5-methoxycarbonylmethyluridine (mcm5U34), and 5-methoxycarbonylmethyl-2-thiouridine (mcm5s2U34) at wobble position in tRNA. These modified nucleosides are important for efficient decoding during translation. In a recent publication, Elongator complex was implicated to participate in telomeric gene silencing and DNA damage response by interacting with proliferating cell nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 44 publications
4
98
0
Order By: Relevance
“…BElongator^, a multimeric protein complex with methyl-transferase activity, participates in the first steps. BElongator^is also related to other cellular processes, such as elongation by RNA polymerase II, histone acetylation, telomeric gene silencing, and DNA repair (Chen et al 2011;Karlsborn et al 2014). Noteworthy in yeast, the phenotype produced by a defective U34 modification (morphological and growth alterations) was reverted by the overexpression of the involved tRNA (Klassen et al 2016b).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…BElongator^, a multimeric protein complex with methyl-transferase activity, participates in the first steps. BElongator^is also related to other cellular processes, such as elongation by RNA polymerase II, histone acetylation, telomeric gene silencing, and DNA repair (Chen et al 2011;Karlsborn et al 2014). Noteworthy in yeast, the phenotype produced by a defective U34 modification (morphological and growth alterations) was reverted by the overexpression of the involved tRNA (Klassen et al 2016b).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Alterations of other modifications at position 34 such as ncm 5 Um 34 result in sensitivity to the aminoglycoside antibiotic paromomycin that causes misreading of near cognate codons (Kalhor and Clarke 2003). Some of the subunits of the enzyme responsible for ncm 5 Um 34 and ncm 5 s 2 U 34 modification were previously identified as components of the elongator complex that functions in transcriptional elongation, silencing at telomeres, and DNA damage response; it since has been shown that the phenotypes are indirect consequences of wobble position errors in translation of proteins that function in these processes (Chen et al 2011). Similarly, mutations of genes encoding proteins of the KEOPS complex cause growth defects and telomere shortening.…”
Section: Removal Of 59 Leader and 39 Trailer Sequences From Pre-trnasmentioning
confidence: 99%
“…The mcm 5 modification is catalyzed by the elongator (ELP) pathway and requires the Elp3/ELO3 catalytic subunit, i.e. a [4Fe-4S] protein Paraskevopoulou et al, 2006;Selvadurai et al, 2014), together with the Trm9/Trm112 complex, which is a tRNA methyltransferase necessary for the last step of mcm 5 formation (Kalhor and Clarke, 2003;Chen et al, 2011;Leihne et al, 2011). The presence of the mcm 5 chain is necessary for an effective thiolation of tRNAs (Leidel et al, 2009;Chen et al, 2011).…”
mentioning
confidence: 99%
“…Although in vivo data are scarce, tRNA modifications might have a regulatory function, because certain open reading frames (ORFs) are enriched in codons recognized by modified tRNAs. In yeast, genes involved in the DNA-damage response are enriched in GAA, AAA, and CAA codons and elongator mutants defective in mcm 5 s 2 modification are hypersensitive to DNA stress (Chen et al, 2011).…”
mentioning
confidence: 99%